Practice of Settling Joint Property: A Review Based on The Islamic Law Compilation - Andra Sanjaya; Muhibbussabry Muhibbussabry (Batulis Civil Law Review)
Introduction: Joint property is property obtained during marriage and is an important object in divorce settlement. In practice, joint property settlement is often carried out amicably without going through the courts.